Factors Causing the Decline of Islam-Based Political Parties Existence on General Elections 2014 - Aclandea, Rahmiana; Elyta, Elyta; Al Qadrie, Syarif Redha Fachmi; Almunawar, Mohammad Nabil (Journal of Modern Islamic Studies and Civilization, 2024)
The dynamics of the existence of Islamic political parties on the historical stage of democracy in Indonesia have experienced unstable political dynamics. This is inseparable from the plurality of Indonesian society which does not only contain Muslims but is diverse with a diversity of other religions. This dynamic can be seen in the track record of participation of Islamic political parties in general elections in Indonesia. The vote share of Islamic political parties, which has tended to decline since the reform era, is a matter of note and homework to be completed immediately. Many factors certainly contribute to the small number of Islamic political parties' votes. Party characteristics and ideology are at stake in society's assessment of the existence of Islamic political parties.